The Right to Life and Other Fundamental Civil Rights of the Child in the Case Laws of the Council of Europe Bodies - Lis, Wojciech (Children’s Rights in Regional Human Rights Systems, 2024)
Life is a condition of human existence and of all freedoms and rights belonging to human beings from conception. These values lose their meaning when there is no reference subject, which is a human being, regardless of the stage of life – prenatal or postnatal. Although not without reservations, this truth has been confirmed in the jurisprudence of the European Commission of Human Rights and the European Court of Human Rights, and is regarded as an important element in shaping contemporary standards for the protection of human rights. The member States of the Council of Europe are obliged to effectively safeguard and protect the right to life. Closely linked to the right to life is the right to respect private and family life, which raises a number of specific issues concerning both the child and its relationship with its parents. This study aims to identify how the right to life of a child from conception and selected rights falling within the concepts of private and family life are understood by convention bodies. Keywords: human life, conceived child, private and family life, child welfare, biological identity, parental authority